Пелагея и красный петух: роман в 2 т. (Б. Акунин) - Акунин Б. (Провинциальный детективъ, 2004)
Экземпляры: аб. ЦБ (2008) / Инвентарный номер: 54858z1 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: А 44 / ББК: 84(2Рос=Рус)6